RAS1 is Involved in the Antifungal Resistance of Candida Albicans and the Inhibition of Farnesol to the Resistance of Biofilms - Zuo, Lulu; Zhang, Zhenzhen; Duan, Wei; Huang, Yun; Xu, Zheng; Zhang, Qinqin; Lv, Ying; Wei, Xin (Archives of Clinical and Biomedical Research, 2022)
Background: Farnesol enhances the susceptibility of Candida albicans biofilms to antifungals; however, its molecular mechanisms are poorly understood. RAS1 is required for the hyphal growth. This study hypothesized that RAS1 is involved in the antifungal resistance of C.albicans and the inhibition of farnesol against biofilms. Methods: The antifungal resistances of C.albicans biofilms formed by RAS1 mutant and control strains were examined using spot assays and XTT reduction assays with and without farnesol, and morphological changes were observed using CLSM and SEM. Meanwhile, RAS1 gene and RAS1 protein in biofilms exposed to farnesol were analyzed using RT-qPCR and Western blot. Results: Compare with control strain, RAS1 overexpressing strain (RAS1OE) was more resistant to some of the antifungal drugs, while RAS1 deleted strain (RAS1Δ/Δ) was less resistant to all antifungal drugs. RAS1 was down-regulated in the C.albicans biofilms exposed to farnesol. The increased resistance of RAS1OE to antifungals was significantly decreased by farnesol, and farnesol decreased the resistance of RAS1OE more obviously than wild-type and RAS1Δ/Δ strains (P<0.05). Further, farnesol reduced the expression of RAS1 in RAS1OE biofilm more obviously than that in wild-type strain biofilm. In addition, morphological observation showed that RAS1OE increased the hyphal growth of biofilm, while RAS1Δ/Δ reduced that, and the inhibition of hyphal growth by farnesol was more obviously in RAS1OE biofilm, while that was less obvious in RAS1Δ/Δ biofilm. Conclusions: